2015
DOI: 10.1007/s10611-015-9585-3
|View full text |Cite
|
Sign up to set email alerts
|

People power and anti-corruption; demystifying citizen-centred approaches

Abstract: In recent years there has been an ever expanding body of work that advocates putting the citizen at the centre of attempts to tackle corruption. The task of anti-corruption policy, so the argument goes, is to empower citizens to act against those who behave in a corrupt fashion. This article illustrates that whilst there is much to be said for encouraging citizens to move against corrupt officials, and citizen-centred anti-corruption ideas subsequently appear attractive in theory, implementing these notions (a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 45 publications
0
7
0
1
Order By: Relevance
“…2. In fact, this is perhaps one of the main shortcomings of any citizen-centered approach to combat corruption (see, e.g., Verdenicci and Hough 2015). See also Marquette andPeiffer 2015 andAlatas 1999.…”
Section: Figurementioning
confidence: 99%
“…2. In fact, this is perhaps one of the main shortcomings of any citizen-centered approach to combat corruption (see, e.g., Verdenicci and Hough 2015). See also Marquette andPeiffer 2015 andAlatas 1999.…”
Section: Figurementioning
confidence: 99%
“…Fox (2015) arguing that bottom-up collective approach on many occasions lacks information, monitoring often lacks bite due to local elite influence and official approach capture by local elites. Similarly, Verdenicci and Hough (2015) also found that these citizen-centered approach easily lose their direction due to coordination and greatly influenced by elite capture. All these problems of bottom-up approach on many occasions directed towards catastrophe.…”
Section: Mentioned That;mentioning
confidence: 89%
“…Public participation is defi ned as involvement of individuals/groups that are aff ected by a proposed intervention subject to a decision-making process (World Bank, 2006;Cho & Ho, 2018). According to Verdenicci and Hough (2015), when citizens were encouraged to act as whistle-blower reporting any experiences of corruption through a participatory initiative, corruption may well be discovered. For example, Bhargava (2015) presented the results of public participation in diff erent countries and showed that a variety of citizens' activities can have diff erent effects at diff erent levels and dimensions.…”
Section: Public Participationmentioning
confidence: 99%